Pengaruh Kualitas Pelayanan Terhadap Kepuasan Siswa (Studi Pada Smk Ganesha Tama Boyolali) - Hidayat, Dwika Wahyu, Lukman Hakim, SE, MSi (2016)
This study aims to determine whether the quality of service affect the satisfaction of students in vocational Ganesha Tama Boyolali and analyze the most dominant factor in influencing student satisfaction in the vocational Ganesha Tama Boyolali. The population in this study were students at SMK Ganesha Tama Boyolali. Samples taken as many as 89 respondents using simple random sampling technique., Which is taking a sample of the population do members queried randomly without regard to strata that exist in the population. Based on the research results, obtained the following regression equation : Y = 3,295 + 0,222X1 + 0,146X2 + 0,279X3 + 0,245 X4 + 0,211X5. Based on statistical data analysis, indicators in this study are valid and are reliable variables. In the classic assumption test, regression model multicoloniarity free, does not occur heteroskedastisitas, and normal distribution. The sequence individually from each of the variables is a significant positive is variable responsiveness with a regression coefficient of 2.141 with sig. 0,035 smaller than 0.05. While no significant positive variables are variables guarantee with a regression coefficient of 1.717 with sig. 0.090 greater than 0.05. Physical evidence variable with a regression coefficient of 1.457 with sig. 0.149 greater than 0.05. Variable empathy with a regression coefficient of 1.406 with sig. 0.164 greater than 0.05. The latter variable reliability with a regression coefficient of 0.820 with sig. 0.415 greater than 0.05. SMK Ganesha Tama Boyolali need to retain the elements that have been rated by customers as well as the need to fix the things that are lacking. Key words: quality of service, physical evidence, reliability, responsiveness, assurance, empathy, student satisfaction.